Hepatology mentorship: A bold idea: Data from the emerging liver scholars program. Issue 1 (12th December 2017) - Lindenmeyer, Christina C.; May, Elizabeth
Abstract : Six years ago, the American Association for the Study of Liver Disease (AASLD) launched an innovative mentoring program, the Emerging Liver Scholar (ELS) Program to provide uncommitted medicine, surgery, pediatric, pathology or radiology residents an opportunity to attend the annual Liver Meeting. An AASLD member guides each ELS as mentor before, during and after the meeting. This article presents promising ELS outcomes from the viewpoint of a mentee and mentor.